EFFECT OF DOPAMINE ON PORTAL BLOOD FLOW IN CIRRHOTIC PATIENTS - Nadir KAYA; Osman YEŞİLDAĞ; Hakkı KAHRAMAN; Celalettin DEMİRCAN; Ülkü YALÇINTAŞ; Sait KAPICIOĞLU (Turkish Journal of Gastroenterology, 2020)
-